The Role of Nurses in Implementing Nursing Care Through Service Training in Padang City - Deni Maisa Putra; Silvia Nency (CV. Get Press Indonesia, 2024)
The role of nurses as direct patient care providers is crucial in the healthcare system. Very high expertise is required for this job, both technical and non-technical. To maintain and improve the quality of health services, nurses must continuously acquire knowledge and skills through organized and continuous in-service training (Aulia et al., 2023; Teniwut, 2023). Nursing in-service training effectiveness will be assessed in this study using a quasi-experimental method. In order to assess the impact of training on nurses' abilities and performance in delivering nursing care, this design makes it possible to compare nurses who receive training with those who do not in a straightforward manner. According to the study, 65 nurses (58 percent) had a good understanding of nursing services, while 47 nurses (42%) had a fair understanding. Before the training, 47 patients (59%) were satisfied with the nursing services they received, while 31 patients (41%) were dissatisfied. The data demonstrated an improvement in patient satisfaction following training and reinforcement, with 59 patients (68%) feeling satisfied and 27 patients (32%) feeling less satisfied. When compared to baseline data, this demonstrates a significant increase in patient satisfaction, suggesting that nursing service training can improve patients' quality of life. Structured and continuous nursing service training is essential to improve nurses' competence and the quality of services provided to patients. This training not only improves patient satisfaction but also increases nurses' confidence and their professionalism in carrying out their duties.